Tear film assessment by using anterior segment OCT in patients with juvenile rheumatoid arthritis - Shewikar Abdelalim Mahmoud Aly; Ahmed Atef Zaki; Ghada Ismail Gawdat; Rasha Mounir Eltanamly (Cairo : Shewikar Abdelalim Mahmoud Aly, 2017)
The aim of this study is to determine the association between juvenile idiopathic arthritis and kerato-conjunctivitis sicca and to assess the cyc dryness using Anterior segment optical coherence and comparing these results with schirmer and tear break up time. Methodology: The study was conducted on S0 eyes of juvenile idiopathic arthritis patients, to assess the cyc dryness. The dryness was neasured by anterior segment OCT. Schirmer test and tear break up time. Results: Juvenile idiopathic arthritis patients suffer from keratocnjunctivitis sicca. Evaluation of the tear meniscus height by ASOCT is considered useful non-contact non-invasive method for measurement of dry cyc. Conclusion: Keratocnjunctivitis sicca is not uncommon in juvenile idiopathic arthritis patients. Examination of ocular dryness by ASOCT for TMH is a valuable non-invasive and non-contact method for evaluation of the tear volume
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Ophthalmology
Issued also as CD
Keywords: Anterior Segment Optical Coherence Tomography; Juvenile idiopathic arthritis; Keratocnjunctivitis sicca